Factors affecting land transfer function and its impact on farmers' income in Srigading Village, Sanden Sub-district, Bantul Regency - Wenang Anurogo; Muhammad Zainuddin Lubis; Hanah Khoirunnisa (Universitas Negeri Malang, 2019)
Coastal area is a specific area where the region can be used as a tourist area, settlements, and agriculture. Some forms of utilization in the field of agriculture, among others, is farming of paddy fields or fishery ponds. As is the case along the southern coast of the Special Territory of Yogyakarta. Coastal residents of Bantul and Kulon Progo districts utilize coastal land as dryland farming and fishery ponds. This study aims to determine the effect of land use change in the Srigading Village (especially for the conversion of shrimp ponds) to the farmers' income in the Village. This research uses the tools of remote sensing technology to identify land use change that happened in the research area and combine with interview result data to know earnings difference from a farmer. The result of the analysis shows that land use in the coastal area of Srigading Village, Sanden Sub-District, Bantul Regency, before being used as shrimp pond is dominated by agricultural land and garden/moor. There are also settlements, and bodies of water contained in the study area. Land in the form of gardens/moor and agricultural land is a land that has the potential to switch function to shrimp farms as long as get enough brackish water supply. The distance is quite close to the beach and the river makes the land is very potential to switch functions into ponds. The results of the analysis also showed that farmers' income before and after shrimp farming in Srigading village experienced an average increase of almost 50%.Kawasan pesisir merupakan wilayah yang berpotensi mengalami perubahan penggunaan lahan. Penduduk pesisir Kabupaten Bantul dan Kulon Progo memanfaatkan lahan pesisir sebagai pertanian lahan kering dan kolam perikanan. Penelitian ini bertujuan untuk mengetahui pengaruh perubahan penggunaan lahan di Desa Srigading (terutama untuk konversi tambak udang) terhadap pendapatan petani di desa. Penelitian ini menggunakan alat teknologi penginderaan jauh untuk mengidentifikasi perubahan penggunaan lahan yang terjadi di daerah penelitian dan digabungkan dengan data hasil wawancara untuk mengetahui perbedaan pendapatan dari petani. Hasil analisis menunjukkan bahwa penggunaan lahan di wilayah pesisir Desa Srigading, Kecamatan Sanden, Kabupaten Bantul, sebelum digunakan sebagai tambak udang didominasi oleh lahan pertanian dan kebun/tegalan. Ada juga pemukiman, dan area air yang terdapat di wilayah studi. Kebun/tegalan dan lahan pertanian adalah lahan yang berpotensi untuk beralih fungsi ke tambak udang selama mendapat pasokan air payau yang cukup. Jaraknya yang cukup dekat dengan pantai dan sungai menjadikan tanah sangat potensial untuk beralih fungsi menjadi kolam. Hasil analisis juga menunjukkan bahwa pendapatan petani sebelum dan sesudah budidaya udang di desa Srigading mengalami peningkatan rata-rata hampir 50%.DOI: http://dx.doi.org/10.17977/um017v24i12019p034